Imagined Violence and Soft Gender: Proposing New Conceptual Categories in Gender Discourses of Indonesian Ethnic Practices - Ikhlasiah Dalimonthe; Yuanita Aprilandini Siregar; Prima Yustitia Nurul Islami; Afdhal (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study explores how Indonesian ethnic communities construct gender meanings distinct from Western notions of rigid roles and domination–subordination. Focusing on Batak, Javanese, and Bugis women, it analyzes how cultural, religious, and social practices internalize gender values and how the categories of imagined violence and soft gender operate in everyday life. Conducted between June and September 2022, the research applied a qualitative exploratory approach through in-depth interviews, participant observation, and cultural document analysis, supported by discourse and semiotic interpretation with triangulation. Findings reveal flexible and contextual gender understandings: Batak women maintain ritual roles despite male political dominance, Javanese women embrace nrimo yet access equal education, and Bugis women embody siri’ na pacce that binds family honor while granting social authority. Imagined violence emerges as a symbolic, consensual restriction, while soft gender reflects voluntary domestic roles shaped by collective consensus. The study formulates soft gender as a novel analytical category, reconceptualizes imagined violence in multi-ethnic contexts, advances Southern Feminisms theoretically, and offers inclusive policy insights practically.